PENERAPAN METODE ROBERT PADA DETEKSI TEPI CITRA SPLIT UNDERWATER - Barus, Ofnika Febrina Br (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
The edge of the image that is difficult to detect by the eye will reduce the beauty of the image, one of these problems occurs in the split underwater image, where the edge of the image is difficult to obtain directly by the eye because in taking the image is directly related to water, and to overcome problems It is necessary to do edge detection in the underwater split image. The Robert method can help to detect edges from split underwater imagery. The use of vb net 2008 will speed up the edge detection process to be carried out by applying the Robert method. Robert's method works by detecting the edges of the vertical part and detecting the edges of the horizontal part of the color image that has been converted into a grayscale image, then the results of edge detection from the two parts are summed up as the final result. -tit to form like lines from the edges of each object contained in an image. From these lines will be obtained the actual forms of each object contained in an image.